the effect of sand training on developing speed endurance among advanced handball players - الشمري, حيدر غازي عزيز (Wasit Journal of Sports Sciences, 2025)
Abstract of the research: The importance of the research lies in training in the sand to develop the speed endurance of advanced handball players. There are also important physical abilities through which many skills specific to the game of handball can be performed, whether defensive or offensive, especially speed endurance, because the game of handball is the majority of its skills. It requires very high and frequent speeds so that the player can continue performing at high speed and for the longest possible period to overcome the burdens and obstacles he faces while playing. Abstract of the research: The importance of the research lies in training in the sand to develop the speed endurance of advanced handball players. There are also important physical abilities through which many skills specific to the game of handball can be performed, whether defensive or offensive, especially speed endurance, because the game of handball is the majority of its skills. It requires very high and frequent speeds so that the player can continue performing at high speed and for the longest possible period to overcome the burdens and obstacles he faces while playing. The problem of the research is that endurance of speed is one of the most important physical abilities that handball players need at the present time because all handball skills must be performed quickly and for the longest possible period during the match. We note that there are many matches that cannot be won because there is a defect in the physical aspects, including endurance of speed. Therefore, the researcher decided to study this problem and show its importance in the game of handball. As for the objectives of the research, they are to prepare exercises on the sand to develop endurance of speed and to know the effect of the exercises on the research sample. As for the hypothesis of the research, it is There are statistically significant differences between the pre- and post-tests of the research sample. The researcher used the single-group experimental method with two pre- and post-tests. The results were processed statistically and presented and discussed. The most important conclusions were that the sand exercises carried out by the experimental group achieved development in (speed endurance) among the players. The most important recommendations are to use exercises on sandy ground by trainers to develop speed endurance.
Keywords: sand training, developing speed, handball